Adaptive Parenting Among Low‐Income Black Mothers and Toddlers' Regulation of Distress. Issue 6 (3rd September 2020) - Bocknek, Erika L.; Richardson, Patricia A.; McGoron, Lucy; Raveau, Hasti; Iruka, Iheoma U.
Abstract : Parenting differs in purpose and strategy according to cultural background (Brooks‐Gunn & Markman, 2005; Iruka, LaForett, & Odom, 2012). The current study tests a unique latent factor score, Adaptive Parenting, that represents culturally‐relevant, positive parenting behaviors: maternal coping with stress through reframing, maternal scaffolding of toddlers' learning during a low‐stress task, and maternal commands during a high‐stress task. Participants were Black mothers ( N  = 119; M age  = 27.78) and their 24‐ to 30‐month‐old toddlers. Families were part of a broader study examining family resilience among urban, low‐income young children and their families. Results demonstrate that the proposed variables align on a single factor and positively predict toddlers' emotion regulation. Findings are discussed in the context of Black culturally‐specific parenting processes.